The influence of religiosity on financial reporting quality across countries - Adem, Abdellatif (Economic and business review, 2026)
This study examines the connection between religiosity and earnings quality, employing accrual-based and real earnings management as key indicators. By analyzing data from 22 countries from 2020 to 2023, the study identifies a negative correlation between religiosity and earnings manipulation, suggesting that managers in more religious environments are less prone to such practices. The robustness of these results is validated through multiple methods and alternative religiosity metrics. Furthermore, the study highlights the role of legal systems in shaping this relationship, demonstrating that managers in religious nations governed by civil law are more likely to engage in earnings management. This study underscores the need for greater awareness of earnings management, particularly in religious nations with a civil-law legal origin. Additionally, it builds on Yamen et al. (2021) by recommending further investigation into cultural influences beyond Hofstede's framework.
Keywords: cultural heritage; kulturna dediščina; legislation; management; religija; religion; zakonodaja